1989
DOI: 10.7326/0003-4819-110-11-867
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, Fat Distribution, and Cardiovascular Risk

Abstract: Intra-abdominal fat deposition constitutes a greater cardiovascular risk than obesity alone. Hyperinsulinemia may constitute an important component of the increased cardiovascular risk of abdominal obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
182
3
7

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(203 citation statements)
references
References 36 publications
11
182
3
7
Order By: Relevance
“…However, in the multiple logistic regression model, the association between intra-abdominal fat and coronary heart disease was no longer significant possibly due to the strong association of intra-abdominal fat with both fasting C-peptide and triglyceride. A recent study confirms the significant association of the intra-abdominal fat area determined by computed tomography with both insulin and triglyceride in a healthy population [32]. In another study intra-abdominal fat area determined by computed tomography was correlated to various plasma lipoprotein levels independent of body mass index [35].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, in the multiple logistic regression model, the association between intra-abdominal fat and coronary heart disease was no longer significant possibly due to the strong association of intra-abdominal fat with both fasting C-peptide and triglyceride. A recent study confirms the significant association of the intra-abdominal fat area determined by computed tomography with both insulin and triglyceride in a healthy population [32]. In another study intra-abdominal fat area determined by computed tomography was correlated to various plasma lipoprotein levels independent of body mass index [35].…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, the association of obesity with coronary heart disease appears to be mediated by other risk factors [13]. Several studies have suggested that site specific body fat measurements may be a better predictor of CHD than overall obesity or adiposity [13,[31][32][33]. In particular, measurements of upper body or central fat, such as subscapular skinfold thickness, the ratio of various skinfold thicknesses, and the waist to hip circumference ratio, have been reported as being significantly associated with coronary heart disease independent of body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Body mass index (BMI), ie the ratio between body weight and the square of body height, is the commonly used continuous variable to assess bodily mass in epidemiological studies, since it corrects for height. 8,9 Overweight is defined by a BMI equal to or higher than 25 kg/m 2 .…”
Section: Body Weight Evaluationmentioning
confidence: 99%
“…[1][2][3] In patients with essential hypertension, insulin resistance may be exacerbated by antihypertensive drug therapy, mainly when diuretics and beta-blocking agents are involved. [4][5][6][7][8] Resistance to insulin is also a predictor of cardiovascular complications, particularly for the coronary circulation. 1,5,6,9,10 The ratio between ankle on brachial systolic blood pressure (ABI) is a well established index allowing bution, but also with the usual biological features of resistance to insulin: plasma triglycerides and cholesterol; plasma glucose and insulin; and plasminogen activator inhibitor (PAI) antigen.…”
Section: Introductionmentioning
confidence: 99%